Genre transgression in interactive works - Claus A. Foss Rosenstand (Akademisk Kvarter, 2011)
A similar formalist interest governs Claus A. Foss Rosenstand'sarticle Genre Transgression in Interactive Works, where Rosenstand argues for the genre transgression of interactive works as creating what he refers to as the simulative genre, characterized by the transformation of the communicator into a simulator, thus creating a framework for analysing any interactive text.